Sexual concerns of cardiac patients: Predictors and the influence of specific sexual activities. (February 2015) - Mosack, Victoria; Hill, Twyla J; Steinke, Elaine E
Background: Addressing sexual concerns of cardiac patients is integral to comprehensive patient-centered nursing care, and instruments for use across cardiac populations are needed to promote this activity. Knowing the factors that contribute to sexual concerns provides insights that help to promote inclusion of assessment of relevant sexual activity and provide sexual counseling as a standard of care. Aim: This study examined demographic factors, comorbid conditions, and sexual activities as predictive of sexual concerns. Specific sexual activities and demographic variables were also examined for their relation to sexual concerns. Methods: This study was a sub-analysis of a cross-sectional observational study testing a regression model of factors that predicted sexual concerns in a broad sample of cardiac patients in the United States, using a self-report survey method. Results: More comorbidities and types of sexual activities contributed to greater sexual concerns reported by respondents. Sexual activities resulting in overall sexual concerns included hugging/kissing, oral sex, and finger penetration. Non-Whites reported more sexual concerns, sexual fears, and symptoms related to sexual activity. Those who were not working/retired from employment reported significantly more sexual concerns and dysfunction, whereas, those who had a smoking/tobacco use history reported more sexual concerns, symptoms, and dysfunction. Conclusion: This study underscores that cardiac patients across a variety of diagnoses and comorbidities often experience sexual concerns, fears, symptoms, and dysfunction. The strongest predictors of sexual concerns were the number of cardiac and noncardiac comorbidities, thus illustrating the importance of a thorough assessment of these factors when examining sexual concerns of cardiac patients.